Gated Communities: Inter- and Intraspecific Diversity of Endosymbionts Across Four Sympatric Aphid Species - Henry, Youn; Brechbühler, Esther; Vorburger, Christoph (Frontiers in Ecology and Evolution, 2022)
Aphids have evolved tight relationships with heritable endosymbionts, i.e. bacteria hosted within their tissues. Besides the primary endosymbiont Buchnera aphidicola, aphids host many facultative secondary endosymbionts with functions they may or may not benefit from. The different phenologies, lifestyles, and natural enemies of aphid species are predicted to favor the selection for distinct endosymbiont assemblages, as well as the emergence of intra-specific genetic diversity in the symbiotic bacteria. In this study, we 1) investigated the diversity of endosymbionts associated with four species from the genus Aphis in the field, and 2) we characterized the genetic diversity of Hamiltonella defensa, an endosymbiont that protects aphids against parasitoid wasps. We observed strong differences in the composition of endosymbiont communities among the four aphid species. Hamiltonella defensa was clearly the dominant symbiont, although its abundance in each species varied from 25 to 96%. Using a multilocus sequence-typing approach, we found limited strain diversity in H. defensa. Each aphid species harbored two major strains, and none appeared shared between species. Symbiont phylogenies can thus help to understand the (seemingly limited) mobility of endosymbionts in aphid communities and the selection forces driving strain diversification.